Uniparental Genome Elimination in Australian Carp Gudgeons. (16th February 2021) - Majtánová, Zuzana; Dedukh, Dmitrij; Choleva, Lukáš; Adams, Mark; Ráb, Petr; Unmack, Peter J; Ezaz, Tariq
Abstract: Metazoans usually reproduce sexually, blending the unique identity of parental genomes for the next generation through functional crossing-over and recombination in meiosis. However, some metazoan lineages have evolved reproductive systems where offspring are either full (clonal) or partial (hemiclonal) genetic replicas. In the latter group, the process of uniparental genome elimination selectively eliminates either the maternal or paternal genome from germ cells, and only one parental genome is selected for transmission. Although fairly common in plants, hybridogenesis (i.e., clonal haploidization via chromosome elimination) remains a poorly understood process in animals. Here, we explore the proximal cytogenomic mechanisms of somatic and germ cell chromosomes in sexual and hybrid genotypes of Australian carp gudgeons ( Hypseleotris ) by tracing the fate of each set during mitosis (in somatic tissues) and meiosis (in gonads). Our comparative study of diploid hybrid and sexual individuals revealed visually functional gonads in male and female hybrid genotypes and generally high karyotype variability, although the number of chromosome arms remains constant. Our results delivered direct evidence for classic hybridogenesis as a reproductive mode in carp gudgeons. Two parental sets with integral structure in the hybrid soma (the F1 constitution) contrasted with uniparental chromosomal inheritance detected in gonads. The inheritance mode happens through premeiotic genome duplication of the parental genome to be transmitted, whereas the second parental genome is likely gradually eliminated already in juvenile individuals. The role of metacentric chromosomes in hybrid evolution is also discussed.